Link Technology to Your Long-Term Business Goals How to Use Technology to Mobilize Your People, Strategy and Operations - Praz. (Berkeley, CA : Apress : Imprint: Apress, 2022)
Link the use of technology with long-term business goals to optimize the core elements in your organization: people, strategy, and operations. This book will show you how effective planning of processes and execution of strategies with the help of technology can bring about an organization-wide increase in productivity and performance. Business environments have grown increasingly competitive. Before an organization realizes what has happened, it can lose or gain market share. Being agile is the key to success. This book covers the processes that can help your enterprise be agile and follow best practices when executing your business strategy. You'll review case studies from real-world experiences that dive deep into the problems a business encounters and the ways to solve those challenges. They deal with the different ways in which your organization can achieve dramatic performance improvements by changing your company's processes. The book also explains how objectives and key results can be used to align business teams for increased productivity. With Use Tech to Mobilize Your People, Strategy, and Operations you'll learn how the intensity of core processes can ensure that growth does not wane in your organization. .
Part 1: People -- Chapter 1: Teams and Divisions -- Chapter 2: Hiring -- Chapter 3: Upskilling -- Chapter 4: People Management -- Chapter 5: Rewards and Recognition -- Chapter 6: People Processes -- Chapter 7: Rituals -- Part 2: Strategy -- Chapter 8: OKR Review -- Chapter 9: Setting up OKRs -- Chapter 10: Linking OKRs to Strategy -- Chapter 11: Ensuring Execution of Strategy -- Chapter 12: OKRs as a Continuous Process -- Part 3: Operations -- Chapter 13: People and Processes -- Chapter 14: Prototyping and Solutioning -- Chapter 15: Scaling Operations -- Part 4: Technology -- Chapter 16: Technology Team Divisions -- Chapter 17: Technology Stack -- Chapter 18: Key Processes and Rituals of Technology Team -- Chapter 19: Business Analytics and its Importance in Scaling and Execution -- Part 5: Processes -- Chapter 20: Data Security -- Chapter 21: Why Do Businesses Fails -- Chapter 22: Exemptions to Processes Good or Bad -- Chapter 23: Processes as a Speed Booster not a Speed-breaker -- Chapter 24: Are Processes Sacred -- Chapter 25: Conclusion.
Keywords: Strategic planning; Leadership; Executives-Training of; Business; Management science; Data protection; Artificial intelligence; Software engineering; Business Strategy and Leadership; Management Education; Business and Management; Data and Information Security; Artificial Intelligence; Software Engineering